The therapeutic response of feline mammary fibroepithelial hyperplasia to aglepristone: A case report - Primma, Naruenath; Vejpattarasiri, Thitapa; Sukprasert, Phasutpon; Nakhern, Siriporn (Journal of Mahanakorn Veterinary Medicine, 2025)
Feline Mammary Fibroepithelial Hyperplasia (FMFH) is a non-neoplastic condition most commonly found in intact female cats, particularly after ovulation or following exposure to exogenous progesterone. The pathogenesis involves the stimulation of progesterone receptors in mammary epithelial and stromal cells, together with the influence of local growth factors such as IGF-1 and EGF. This combined effect leads to rapid cellular proliferation and inhibition of apoptosis. This case report describes an intact female cat diagnosed with FMFH following weaning. The cat was treated with aglepristone (AlizinTM, Virbac, Bangkok), a progesterone receptor antagonist, administered subcutaneously at a dose of 10 mg/kg on days 1, 2, 3, 4, and 9. The mammary glands gradually decreased in size within 7–10 days, with clinical improvement. Adjunctive therapies, including anti-microbial, anti-inflammatory drugs, and topical cool compresses, were also implemented to manage local inflammation. These findings support the use of aglepristone as an effective treatment for FMFH in cats, particularly when ovariohysterectomy (OVH) is not immediately feasible for the owners. Nevertheless, to prevent recurrence, OVH is recommended once the condition has resolved, as progesterone remains the primary trigger for disease reactivation during subsequent estrous cycles.